(untitled) (Cardiovascular Journal, 2013)
Background: It has been found that there is strong association of QT dispersion and QT dispersion ratio with extent and severity of coronary artery disease. Qualitative importance of QTc dispersion on the base line ECG in patients with MI is recognized clinically but quantification of this phenomenon is less commonly used in clinical practice, which might be a better independent risk predictor of this group of patients. Methods: A total of 100 patients were selected, Study populations sub-divided into two groups on the basis of QTc dispersion. In group I (comparison group): QTc dispersion is <60 milliseconds (msec) in group II (study group) : QTc dispersion e60milliseconds(msec). 50 patients in each group. QT dispersion was calculated on standard resting 12 lead ECGs. QT interval was measured from the beginning of the inscription of the QRS complex to the point at which the T wave returned to the isoelectric line. Angiographic severity of coronary artery disease was assessed by- Vessel score, Friesinger score and Leaman score. Interpretation of coronary angiogram was reviewed by at least two cardiologists. . Results: The mean vessel score for group I patients was 1.16±0.68 and that of group II patients was 2.30±0.64 and the mean difference was statistically significant (p<0.05). Patients those had single vessel involvement had mean QTc dispersion 57.05, patients those had double vessel disease mean QTc dispersion was 102.00 and patients those had triple vessel involvement had mean QTc dispersion 177.60. There was a strong positive correlation with the QTc dispersion and increasing number of vessel involvement (Pearsons correlation coefficient). The mean Friesinger score for group I patients was 4.84±2.56 and that of group II patients was 9.80±2.60. The mean difference was significantly (p<0.05) higher in group II patients. There was a strong positive correlation between the QTc dispersion and Leaman score (Pearsons correlation coefficient). In group I patients 56% had insignificant coronary artery disease and 44% had significant coronary artery disease defined by Friesinger index (n=100). In group II patients 6% had Insignificant coronary artery disease & had 94% significant coronary artery disease. Conclusion: QTc dispersion>60 ms had independent predictive value for the severity of coronary artery disease. The greater the QTc dispersion the higher the number of coronary artery involvement. We observed that there is a positive correlation between prolonged QT dispersion and coronary artery disease severity in terms of Vessel score, Friesinger score, Leaman score. DOI: http://dx.doi.org/10.3329/cardio.v5i2.14322 Cardiovasc. j. 2013; 5(2): 173-181